2017
DOI: 10.1111/ffe.12685
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic damage evolution during very‐high‐cycle fatigue (VHCF) of tempered martensitic steel

Abstract: Dimensioning with high-strength steels relies on the knowledge of Wöhler-type S/N data and the assumption that no failure occurs for load levels below the fatigue limit for applications where the number of load cycles exceeds 10 7 .Very-high-cycle fatigue (VHCF) experiments applied to a 0.5C-1.0Cr-Mo tempered steel (German designation: 50CrMo4) revealed surface crack initiation at prior austenite grain boundaries in medium strength condition (37HRC) and internal crack initiation at nonmetallic inclusions at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
(21 reference statements)
5
14
0
Order By: Relevance
“…[7][8][9][10][11] The observed slip band formation occurred primarily near and along PAGBs. This result is in good agreement with the studies by Nishikawa et al, Batista et al, and Krupp et al, [10,11,14] which also reported a slip band formation at PAGBs. Apart from PAGBs, block boundaries are also cited as slip band formation sites.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[7][8][9][10][11] The observed slip band formation occurred primarily near and along PAGBs. This result is in good agreement with the studies by Nishikawa et al, Batista et al, and Krupp et al, [10,11,14] which also reported a slip band formation at PAGBs. Apart from PAGBs, block boundaries are also cited as slip band formation sites.…”
Section: Discussionsupporting
confidence: 93%
“…[9,13] In many studies, the preferential alignment of carbides along microstructural interfaces is cited as a possible reason for intergranular crack initiation and early short crack propagation. [7,14,17,18] In addition, intergranular crack initiation can be explained by the impingement of slip bands on grain boundaries [14,19,20] or the anisotropic elastic and plastic properties of the grains. [11,12,15,[21][22][23] The number of slip bands formed and cracks initiated rises with increasing number of cycles and with increasing stress amplitude.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…very-high-cycle fatigue (VHCF), may still happen in practical industrial applications [1][2][3][4]. VHCF behavior has attracted the attention of researchers in recent decades due to increasingly realistic requirements and scientific interests [5][6][7][8][9]. At present, it has been known that the typical morphology of the internal crack initiation region (CIR) for VHCF of highstrength steels is a fish-eye (FiE) containing a relatively rough region of fine-granular area (FGA), and it surrounds an inclusion which is considered as the origin of the crack initiation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The second problem is that LEFM principles were primarily developed for long cracks, and not for small cracks. Various other strategies have been developed recently …”
Section: Introductionmentioning
confidence: 99%